Analisis Korelasi Kawat Tanah Dengan Tahanan Pentanahan Terhadap Back Flashover - Novri Andrean; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesian is a tropical climate in general, including areas with highlightning days each year. A prominent mountain or tower in the middle of a free area of rice fields, fields, gardens, etc. it has the possibility of a higher radiation than places in the middle of the city surrounded by other tall buildings. The need for electricity is very important. So it needs a reliable system of electric power, service, and continuity of maximum 150 kV High Voltage Air Channels electricity distribution is part of the electric power transmission system. This channel is quite often a direct lightning strike disruption which can result in Back Flashover in the channel. To minimize this disturbance used the Independent Ground Wire System (IGWS) system installed along the 150 kV Transmission Line. Then to determine the correlation of ground wire with the value of tower ground resistance against back flashover due to direct lightning strikes using ATP-EMTP Software. The Simulation results show that the relationship of ground wire with tower ground resistance value is the greater than lightning impulse current and the tower grounding value. The peak voltage on the tower and phase wire increase.The phase voltage of the phase wire which is exposed to the back flashover on the 70 kA lightning impulse with the phase wire voltage of 1.66 MVolt.Keywords: ATP-EMTP, Back Flashover, Ground Wire, Tower grounding value.